Cass Kruger: capstone - Kruger, Cass, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work refers to the human body within the context of gender, sexuality and identity. I explore the vast diversity that exists within these themes and present them in my drawings for the viewer to reflect upon. This piece represents an exploration of the forms and contour of the human body. There are suggestions of identity, sexuality and gender that appear throughout the piece. The reception of these images can be very personal to the viewer, as they are presented in an ambiguous manner, open to interpretation. In order to alleviate the inevitable repulsion some viewers may have to the content of my work, I use enticing and playful formal qualities to make my work more approachable. My soft, whimsical color palate, and simple use of materials and line ease the viewer into a state of child-like wonder. Here they can forget or reflect upon their preconceived notions of what is or isn't vulgar. My work hovers between the mature and the immature. My sumptuous line work and sensual imagery heighten the erotic nature of my work, but the lack of clarity of what's being depicted neutralizes that somewhat, and further pulls in the viewer to examine images that they might usually avoid. There is a fragmented quality in order to convey the uncertainty can exist when trying to define one's identity.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.